British-Canada’s Land Purchases, 1783-1788: A Strategic Perspective - Reimer, Gwen (Ontario History, 2019)
This article examines several of the earliest land purchases in Ontario as phases in a single strategic plan by the British Crown to secure settlement lands and safe communication routes in the aftermath of the American War of Independence. Between 1783 and 1788 British colonial authorities executed a series of right-of-way and land cession agreements with Indigenous nations for lands extending from the St. Lawrence River, westward along the north shore of Lake Ontario, and northward along the historic carrying places linking Toronto, Lake Simcoe and Lake Huron. Viewing the Crawford, Gunshot, Toronto and Matchedash purchases as contiguous in time and space offers both clarity and context to a period of colonial treaty-making in Canada from which few records have survived. Archival holdings contain scant records of proceedings, deeds, maps or boundary descriptions for these treaties. For decades, Indian Affairs officials were concerned about the lack of documentation to validate the terms and extent of these land purchases and it was not until 1923 that the Gunshot and Matchedash surrenders were supposedly confirmed and the boundaries of those tracts encompassed within the terms of the Williams Treaties. For historical researchers, the determination of dates, geography and terms of early colonial treaty agreements remains a challenge. This article contributes both a broader context and greater detail about four such transactions between British authorities and Indigenous nations in southern Ontario in the eighteenth century.